2021
DOI: 10.21426/b636053604
|View full text |Cite
|
Sign up to set email alerts
|

Using citizen science to monitor non-native species: the case of Lethocerus patruelis (Stål, 1855) (Hemiptera: Belostomatidae) in Italy

Abstract: Findings of Lethocerus patruelis (Stål, 1855) in Southern Italy have become frequent in the last decades. We collected records of Lethocerus patruelis observations in Italy using scientific literature, citizen science programs, and social networks as data sources to create a complete and up-to-date dataset. This dataset is made of 59 Lethocerus patruelis observations from the Apulia, Basilicata, Calabria, and Abruzzi regions, 32 of which were previously unpublished, spanning from 1997 to 2020. Half of these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It has also been demonstrated that volunteers can also collect high-quality data (Delaney et al, 2008;Jordan et al, 2012;Lewandowski and Specht 2015;Kosmala et al, 2016), which can also be used for increasing the amount of data available for biogeography studies (Devictor et al, 2010). In the last decade, several biogeographic studies made use of citizen science data (Barahona-Segovia et al, 2021;La Sorte & Somveille, 2021), demonstrating the strategic added value that citizen science can provide to this area of research, also in exploring the distribution of alien invasive species (Lo Parrino & Tomasi, 2021;Nimis et al, 2019). Wang Wei et al (2016), in a wide review, analyse the contribution of volunteers in the study of urban populations of birds and butterflies, stressing the issues related to the use of citizen science data, and highlighting its yet underexploited potential.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that volunteers can also collect high-quality data (Delaney et al, 2008;Jordan et al, 2012;Lewandowski and Specht 2015;Kosmala et al, 2016), which can also be used for increasing the amount of data available for biogeography studies (Devictor et al, 2010). In the last decade, several biogeographic studies made use of citizen science data (Barahona-Segovia et al, 2021;La Sorte & Somveille, 2021), demonstrating the strategic added value that citizen science can provide to this area of research, also in exploring the distribution of alien invasive species (Lo Parrino & Tomasi, 2021;Nimis et al, 2019). Wang Wei et al (2016), in a wide review, analyse the contribution of volunteers in the study of urban populations of birds and butterflies, stressing the issues related to the use of citizen science data, and highlighting its yet underexploited potential.…”
Section: Introductionmentioning
confidence: 99%